STUDI KELAYAKAN ATMOSPHERE PASAR IKAN MODERN SEBAGAI PEMBAHARUAN PASAR IKAN TRADISIONAL (Komparasi Pasar Ikan Modern Muara Baru dan Pasar Grosir Ikan Muara Angke): FEASIBILITY STUDY ATMOSPHERE OF THE MUARA BARU MODERN FISH MARKET AS A RENEWAL OF THE TRADITIONAL FISH MARKET - Roland Ananda; Wahyu Ramandha Putro; Andrea Cecilia (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
Feasibility Study Atmosphere of The Muara Baru Modern Fish Market as a Renewal of The Traditional Fish Market. The Luar Batang Fish Market, which was built during the Dutch colonial administration as Vismarkt, is a fish auction center in Jakarta which has now been relocated because of its very poor condition. The Luar Batang Fish Market Traders were relocated to two places, namely the Muara Angke Wholesale Fish Market and Muara Baru Fish Market to provide a decent place to trade. In 2019, The Muara Baru Fish Market was relocated again and changed its name into Muara Baru Modern Fish Market in response to problems that arise in the traditional fish market. The purpose of this study is to discuss what are the factors that distinguish the atmosphere between traditional and modern fish markets, how the transformation of fish market design has impacts on local communities, traders and buyers, and what are the values that change, remain, lost and arises from the phenomenon of changes in traditional fish market designs into modern ones using the research methods of comparison, continuity and changes, through semiotics.